Long-term efficacy, tolerability and retention rate of azathioprine in 103 aquaporin-4 antibody-positive neuromyelitis optica spectrum disorder patients: a multicentre retrospective observational study from the UK. (October 2014) - Elsone, Liene; Kitley, Joanna; Luppe, Sebastian; Lythgoe, Daniel; Mutch, Kerry; Jacob, Saiju; Brown, Rachel; Moss, Kathryn; McNeillis, Benjamin; Goh, Yee Yen; Leite, M Isabel; Robertson, Neil; et al.
Background: Azathioprine (AZA) is a common immunosuppressive drug used for relapse prevention in neuromyelitis optica (NMO). Objectives: The objective of this paper is to assess efficacy, tolerability and retention of AZA in a large NMO cohort. Methods: We conducted a retrospective review of medical records of 103 aquaporin-4 antibody-positive NMO and NMO spectrum disorder (NMOSD) patients treated with AZA. Results: This is the largest reported cohort of AQP4-Ab positive patients treated with AZA. Eighty-nine per cent ( n = 92) had reduction in median annualised relapse rates from 1.5 (IQR 0.6–4.0) to 0 (IQR 0–0.27, p < 0.00005) with treatment. Sixty-one per cent ( n = 63) remained relapse free at a median follow-up of 18 months. Neurological function improved or stabilised in 78%. At last follow-up, treatment was discontinued in 46% ( n = 47). Of these, 62% ( n = 29) were because of side effects, 19% ( n = 9) because of death, 15% ( n = 7) because of ongoing disease activity, and 2% ( n = 1) because of pregnancy. Using Kaplan-Meyer curves, we estimate that 73%, 58%, 47% and 33% of patients will remain on AZA for longer than one, three, five and 10 years, respectively, after initiation of treatment. Conclusions: AZA is a modestly effective treatment for NMO. However, many patients discontinue AZA over time and this seems to reflect poor tolerability more than lack of efficacy.